ALL IN GOOD TASTE: SAVOR THE FLAVORS OF TAIWANSEBAGAI UPAYAPELAKSANAAN NATION BRANDINGTAIWAN - Rahayu Dian Sari, Ni Luh Putu; Kumala Dewi, Putu Ratih; Prameswari, A.A. Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2020): Hubungan Internasional Vol1, No1, th 2020, 2020)
ABSTRACT   This research is conducted with qualitative research method to compile how Taiwan conducted their gastrodiplomacy program named All in Good Taste: Savor The Flavors of Taiwan as a way to brand the country . Taiwan used several ways to promote the program, including two major strategies, namely the Internationalization Strategy and the International Localization Strategy which lasted until 2013as a tool to show the country’s existence and also to introduce Taiwan's culinary culture. Taiwan conducted the said program as a brand to achieve various goals, including building an image, enhancing the nation's competitiveness, and forming the identity with various cultures and ethnics . Although the impact of the nation branding according to NBI could not be seen properly , and the results obtained from gastrodiplomacy can not be achieved directly,the Taiwanese cuisine was slowly gaining recognition by public .                                                   Keywords: Gastrodiplomacy, Nation Branding, Taiwan